Percepção ambiental sobre mudanças climáticas em comunidades costeiras na Amazônia, ameaças ao bem-estar e sobrevivência local: um estudo na Reserva Extrativista Marinha de Soure, Pará, Brasil - ASSIS, Davison Marcio Silva de (Universidade Federal do Pará, 2025)
Climate change, a global phenomenon with serious consequences for ecosystems, is affecting nature and the human populations that live in it and depend on its goods and services on a large scale, and coastal areas, being more exposed to the effects of this phenomenon, have been affected to an unprecedented extent. The reduction in the services provided by these areas has a direct impact on the way of life of the human populations living there, who have established a relationship of dependence on nature and its resources. The Marine Extractive Reserve of Soure, located on the coast of the Eastern Amazon, is characterized by the fact that it encompasses an area composed of three traditional communities whose way of life is based on a sustainable and subsistence relationship with nature. Despite its location in a protected area and its sustainable practices, the effects of climate change may pose serious threats. In this context, this work, which is characterized as interdisciplinary research, raised perceptions about climate change and sought to understand, in the light of these perceptions, how residents associate changes in the flow of goods and services from coastal ecosystems with this phenomenon. The raised perceptions reveal the high level of agreement for the occurrence of climate change. Although the communities demonstrate sustainable practices in resource use and management, the perceptions indicate that the global impacts of climate change can be felt at the local level and affect the provision of natural resources. High perceptions are shaped by age, length of residence, and degree of dependence on the goods and services of the coastal ecosystem, indicating that people who are older, live longer in one of the communities, and consequently have greater dependence on the resources, are the ones with the highest perceptions. These variables, which explain the high perceptions found, reinforce that the construction of these perceptions is based on traditional knowledge, which is the result of an intense relationship with nature and its resources, safeguarding the history, culture and identity of local peoples.